Incline dependence of the power-duration relationship in cross-country skiing - Horvath, M.; Andersson, E. P.; Kölnas, A.; Spreitz, A.; Boström, H.; Sörfeldt, A.; Kuylenstierna, D. (Frontiers in Physiology, 2025)
Introduction: This study aimed to develop a methodology for establishing the power-duration relationship in cross-country skiers and to investigate the influence of incline on critical power (CP) model parameters.